KEINDAHAN DAN INOVASI DALAM SENI DAN ARSIKTEKTUR ISLAM SEPANJANG SEJARAH - Marwah Khairani (Al-Ikram : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This article discusses the beauty and innovation in Islamic art and architecture throughout history using a historical-critical and comparative approach. The main focus of this study is how Islamic aesthetics not only display spiritual values but also reveal innovative dynamics in techniques and designs, from the early days of Islamic civilisation to the contemporary era. Elements such as geometric patterns, calligraphy, muqarnas, and domes are dominant visual elements that reflect the depth of philosophy and transcendental values in Islamic art. This study uses primary sources from Islamic academic literature, such as documents from UIN Suska and UIN Sunan Gunung Djati, and is enriched with five other scientific references, both from national and international journals. This research demonstrates that Islamic architecture has always evolved by combining aesthetic principles, functional structures, and local contexts. Innovations during the Seljuk and Andalusian periods, as well as the integration of modern digital technologies such as parametric design and artificial intelligence in contemporary architecture, show that Islamic heritage is not static but adaptive and sustainable. These findings reveal the continuity of Islamic values in building and spatial arts, as well as how Islamic identity remains relevant in modern challenges, including sustainability, social function, and spiritual expression. Thus, this article offers conceptual and historical contributions to the discourse on Islamic art and architecture across time.